Environmental Literacy-Based Learning Model: Environmental Education Innovations for the 21st Century Generation - Yuli Ifana Sari; Ika Meviana; Ninik Indawati; Lanyala Trio Agus Muslim (Universitas Lambung Mangkurat, 2026)
This research aims to develop and implement an Environmental Literacy-based learning model as an innovation in environmental education for the 21st century generation at SMAN 1 Dampit. The study is motivated by the relatively low level of students’ environmental awareness and the limited learning approaches that integrate environmental knowledge, skills, attitudes, and responsible behavior within classroom practices. Environmental literacy is considered an essential competence in addressing contemporary environmental challenges and preparing students to become environmentally responsible citizens. Therefore, an innovative and contextual learning model is needed to bridge theoretical understanding and real-life environmental action. This study employed a quasi-experimental method using a pretest–posttest control group design. The research participants consisted of senior high school students who were divided into experimental and control groups. The instruments used in this study included environmental literacy questionnaires covering dimensions of knowledge, cognitive skills, attitudes, and responsive behavior, observation sheets to assess the implementation of the learning model, and learning outcome tests to measure students’ conceptual understanding. Data were analyzed using descriptive statistics, paired t-tests, and independent t-tests to examine differences and improvements in students’ environmental literacy before and after the intervention. The results of the study indicate that the implementation of the Environmental Literacy-based learning model significantly improved students’ environmental knowledge, cognitive skills, attitudes, and pro-environmental behavior compared to conventional learning models. The experimental group showed a higher increase in overall environmental literacy scores, particularly in knowledge and analytical skills, while improvements in attitudes and behaviors demonstrated meaningful progress through experiential and context-based learning activities. These findings highlight the effectiveness of integrating environmental literacy into learning strategies and recommend the incorporation of Environmental Literacy-based learning models into secondary school curricula to support sustainable education and 21st century competencies.